Amniotic-fluid Lactoferrin: A Marker for Subclinical Intraamniotic Infection Prior to 32 Weeks Gestation - Kimberly A. Heller; Phillip C. Greig; R. Phillip Heine (Hindawi Limited, 1995)
Objective: Lactoferrin is a glycoprotein released from the secondary granules of activated neutrophils in the setting of infection. The purpose of this study was to determine if amniotic-fluid (AF) lactoferrin levels are elevated in preterm labor (PTL) patients with subclinical intraamniotic infection (IAI).